How a New Learning Theory Can Benefit Transformative Learning Research: Empirical Hypotheses - Friedman, Joshua (Frontiers in Education, 2022)
Transformative Learning research and practice has consistently stalled on three fundamental debates: 1) what transformative learning is, and how it’s differentiated from other learning; 2) what the preconditions for transformative learning are; and 3) what transformative learning’s predictable and relevant outcomes are. The following article attempts two main feats: 1) to provide a re-organization of transformative learning theory through the work of Vygotskian cultural-historical activity theory, and a newly synthesized meta-theory of learning and development generally, and 2) to use that re-organized model to articulate empirical research questions and hypotheses that are more amenable to observation and analysis than the typical time and cost intensive methods available to most researchers studying transformative learning today. The newly synthesized model draws on historical work in cognitive, social, educational, and clinical psychology, and clearly articulates the dialectical nature between the environment and experience, and what is meant by classical transformative learning concepts such as cognitive-rational frame of reference shifts, self/soul inner work, critical reflection, imaginative engagement, and everything in between.